Influence of Family-Based Characteristics on Trainees’ Completion Rate in Vocational Training Centres in Kenya - Kiplagat , Hoseah; Ferej, Ahmed; Kafu , Patrick (African Journal of Education,Science and Technology (AJEST), 2018)
Lack of parental involvement is one of the major factors that leads to higher dropout rates in a school system. This paper focuses on the influence of family-based characteristics on trainees’ completion rate in Vocational Training Centres (VTCs) in Kenya. Vocational Training Centres (VTCs) were previously referred to as Youth Polytechnics (YPs) up to the year 2013 in Kenya when the country adopted the new name through an Act of Parliament. The study was conducted in five selected VTCs in four counties; Kakamega, Nandi, Elgeyo Marakwet, and Baringo. The study adopted explanatory sequential mixed methods design. The study instruments employed were questionnaires for trainees and instructors, and interview schedules for VTC Managers and County Directors of Youth Training. The study had a sample size of 228 respondents. Survey data was first collected, then followed by organized interviews with the aim of collecting insightful data for this study. Quantitative data was descriptively analyzed and qualitative data was analyzed thematically. The findings from this study revealed that family-based characteristics such as changes in family structures, poor parental influence on the choice of courses in VTCs, low status of trainee parents, high poverty levels, parents not monitoring trainees’ progress in VTC, inadequate parental guidance and counseling, negative parental attitude towards VTCs, among others influenced trainees to drop out of VTCs. Based on these findings, we recommend that parents should urgently provide a leading role in guiding and counseling their children, continuously monitor their children’s progress in VTCs, urgently devise means of earning sufficient income to support their children’s education and have positive attitude towards VTCs.